Analisis kesalahan penggunaan kalimat majemuk dalam menulis karangan narasi peserta didik kelas v sekolah dasar - Angela Raisya Putri Cahyati; Slamet Slamet; Roy Ardiansyah (Universitas Sebelas Maret, 2024)
This research aims to (1) describe the errors in using compound sentences in narrative essays written by fifth-grade students at SDN Karangasem I Surakarta, and (2) describe the factors influencing the errors in using compound sentences in writing narrative essays by fifth-grade students at SDN Karangasem I Surakarta. This study is a descriptive qualitative research. The research subjects are fifth-grade students at SDN Karangasem I Surakarta. Data collection methods include observation, document analysis, and interviews. Data analysis technique uses Tarigan & Tarigan’s error analysis. The research findings show that 143 errors in using compound sentences were identified (52.57%), consisting of 57 errors in using compound sentences (20.96%), 78 errors in using complex compound sentences (28.68%), and 8 errors in using mixed compound sentences (2.94%). Factors influencing the use of compound sentences include (1) mastery of material related to compound sentences, (2) mastery of grammatical rules for compound sentences, (3) proficiency in everyday language, and (4) practice in writing compound sentences. The theoretical implications of this research can be used as a reference for future studies. The practical implications of this research can assist educators in providing an understanding of teaching compound sentence writing